2006
DOI: 10.1002/ajmg.a.31125
|View full text |Cite
|
Sign up to set email alerts
|

A new case of Grange syndrome without cardiac findings

Abstract: Grange syndrome comprises arterial stenoses with hypertension, brachysyndactyly, bone fragility, learning disability, and cardiac defects. To date, we know of two reported families with five affected individuals. We report on one of the youngest cases, in a third family, a 3-year-old girl with brachysyndactyly, renal artery stenosis with hypertension, and bone fragility. She does not have apparent cardiac disease, suggesting cardiac anomalies may not be an obligatory finding in this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Grange syndrome (OMIM 602531) is a recently identified disorder characterized by diffuse arterial occlusive disease, arterial hypertension, congenital cardiac defects, bone fragility, brachysyndactyly, and learning disabilities. It was first reported in four members of a family from United States [Grange et al, 1998] and in two subjects thereafter [Weymann et al, 2001; Wallerstein et al, 2006]. Here, we report on the case of a young female presenting with subarachnoid hemorrhage (SAH), whose pattern of anomalies is consistent with the diagnosis of Grange syndrome.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Grange syndrome (OMIM 602531) is a recently identified disorder characterized by diffuse arterial occlusive disease, arterial hypertension, congenital cardiac defects, bone fragility, brachysyndactyly, and learning disabilities. It was first reported in four members of a family from United States [Grange et al, 1998] and in two subjects thereafter [Weymann et al, 2001; Wallerstein et al, 2006]. Here, we report on the case of a young female presenting with subarachnoid hemorrhage (SAH), whose pattern of anomalies is consistent with the diagnosis of Grange syndrome.…”
Section: Introductionmentioning
confidence: 53%
“…This makes alternative modes of inheritance plausible, including autosomal dominant with incomplete penetrance or parental gonadal mosaicism. Furthermore, the negative family history in two patients previously reported [Weymann et al, 2001; Wallerstein et al, 2006] suggests that sporadic forms may exist. This is probably the case in our patient.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Grange syndrome is a recently described hereditary disorder that is associated with a variable combination of multiple arterial stenoses and aneurysms, brachysyndactyly, bone fragility, learning disability and cardiac defects [14][15][16]. The arterial disease commonly results in a syndrome that resembles fibromuscular dysplasia, with hypertension and angiographic evidence of 'beading'.…”
Section: Grange Syndromementioning
confidence: 98%
“…Grange syndrome (OMIM 602531) is an autosomal recessive condition with severe and early‐onset vascular disease characterized by stenosis or occlusion of arteries, primarily the renal, cerebral and abdominal arteries, along with variable penetrance of brachydactyly, syndactyly, bone fragility, and learning disabilities. After its first report in four members of a family from the United States (Grange et al, ), four additional unrelated cases were subsequently reported (Volonghi et al, ; Wallerstein et al, ; Weymann et al, ). The etiology of Grange syndrome is due to homozygous loss‐of‐function rare variants in YY1AP1 , which encodes a component of the INO80 chromatin‐remodeling complex (Guo et al, ).…”
Section: Introductionmentioning
confidence: 99%